2016
DOI: 10.3892/mmr.2016.5495
|View full text |Cite
|
Sign up to set email alerts
|

miRNA polymorphisms (miR-146a, miR-149, miR-196a2 and miR-499) are associated with the risk of coronary artery disease

Abstract: Small non‑coding microRNAs (miRNAs) are not only important for heart and vascular development but are also important in cardiovascular pathophysiology and diseases, such as ischemia and atherosclerosis‑related diseases. However, the effect of miR‑146a, miR‑149, miR‑196a2 and miR‑499 polymorphisms on coronary artery disease (CAD) susceptibility remain unknown. The aim of the present study was to examine the genotype frequencies of miR‑146a, miR‑149, miR‑196a2 and miR‑499 polymorphisms in patients with CAD, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 46 publications
3
34
0
Order By: Relevance
“…Then, 19 studies including 6 reviews, 12 studies not for focus polymorphisms, and 1 study without available information [22] were excluded. Finally, 12 eligible articles (13 studies) published from 2012 to 2016 were selected in the meta-analysis, including ten studies on microRNA-146a rs2910164 G>C [2332], seven studies on microRNA-196a2 rs11614913 T>C [23, 26, 27, 29, 31, 33], six publications on microRNA-499 rs3746444 A>G [23, 25, 26, 29, 31, 33], and two studies on microRNA-149 rs71428439 A>G [29, 34], respectively. The process of study selection was shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, 19 studies including 6 reviews, 12 studies not for focus polymorphisms, and 1 study without available information [22] were excluded. Finally, 12 eligible articles (13 studies) published from 2012 to 2016 were selected in the meta-analysis, including ten studies on microRNA-146a rs2910164 G>C [2332], seven studies on microRNA-196a2 rs11614913 T>C [23, 26, 27, 29, 31, 33], six publications on microRNA-499 rs3746444 A>G [23, 25, 26, 29, 31, 33], and two studies on microRNA-149 rs71428439 A>G [29, 34], respectively. The process of study selection was shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The process of study selection was shown in Figure 1. Among the retrieved articles, nine articles [23, 24, 2630, 33, 34] were written in English and three [25, 31, 32] in Chinese. Moreover, two of the studies involved Caucasians [24, 30], and eleven of them were conducted for Asians.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To a certain extent, the alteration of rs2292832 T>C in miRNA ‐149 may cause alterations in expression and susceptibility to diseases. For example, Sun et al reported that in a Korean population, some miRNAs and combinations of genotype polymorphisms, such as miRNA‐149 rs2292832 T>C, could contribute to the occurrence of coronary artery disease, a major complication in KD. A study in a Chinese population might obtain similar results.…”
Section: Introductionmentioning
confidence: 99%
“…Six SNPs located in the pre-miRNA regions of miR-146a (rs2910164, rs57095329 and rs6864584), miR-149 (rs2292832), miR-196a2 (rs11614913) and miR-499 (rs3746444) have been identified, using bioinformatic methods, as common SNPs (Hu et al, 2008), and they are considered the genetic predisposition factors for various inflammation-related diseases (Qi et al, 2013). The combined effects of the environmental factors and miR-149, miR-146a and miR-196a2 polymorphism combinations may contribute to the development of coronary artery disease (CAD; Sung et al, 2016). Furthermore, mir-499 was shown to be involved in autoimmune and inflammatory disease progression.…”
Section: Introductionmentioning
confidence: 99%